Ultrafine SnO2 aggregates in interior of porous carbon nanotubes as high-performance anode materials of lithium-ion batteries. (June 2019) - Zhang, Wen; Du, Rui; Zhou, Chenggang; Pu, Song; Han, Bo; Xia, Kaisheng; Gao, Qiang; Wu, Jinping
Abstract: As a promising anode candidate for lithium-ion batteries, tin oxide (SnO2 ) suffers from the pulverization lead by the volume expansion during electrochemical redox. Herein, ultrafine SnO2 nanoparticle aggregates have been successfully impregnated in the interior of porous carbon nanotubes (pCNT) via a simple vacuum-immersion of SnCl4 solution to pCNT powder followed by a vapor-induced hydrolysis. The ultrafine feature of the nano-SnO2 aggregates shortens the diffusion pathways of Li +, and more importantly, significantly reduces the strains during lithiation/delithiation; while pCNT could not only buffer the volume expansion but endow more favorable Li + transportation kinetics at the electrode/electrolyte interfaces. In addition, the mesopores on the wall of carbon nanotubes can not only facilitate the introduction of tin source in the process of material preparation, but also accelerate the diffusion of electrolyte in composite materials. As a consequence, the SnO2 @pCNT composite delivers excellent cyclic stability and superior rate capability. Specifically, a discharge capacity of 968 mA h g −1 can be achieved after 100 cycles at 100 mA g −1 ; in particular, at a high current density of 1000 mA g −1, the capacity could reach as high as 890 mA h g −1 after 500 cycles. Our results provide a highly scalable preparation scheme for fabrication of SnO2 -based anode materials, which may be very referential to develop metal oxide-based lithium-storage electrode materials. Graphical abstract: Image 1 Highlights: Using PMS/Co 2+ procedure to create numerous mesopores on the tube walls of CNTs. The ultrafine nano-SnO2 aggregates was successfully filled in the interior of porous carbon nanotubes. The SnO2 @pCNT composite electrode delivers excellent cyclic stability and superior rate capability.